BLOOD GLUCOSE LOWERING EFFECT OF AQUEOUS LEAF EXTRACTS OF AGERATUM CONYZOIDES IN RATS. - Nyunaï, N.; Njikam, N.; Mounier, C.; Pastoureau, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
This study was undertaken to investigate the effect of aqueous extracts from leaves of Ageratum conyzoides (300mg/kg) on blood glucose in normoglycemic and streptozotocin-diabetic rats. The extract was administered orally and the blood glucose level was measured hourly for 4h. The hypoglycaemic activity was evaluated by comparing with the initial blood glucose level. In streptozotocin-diabetic rats, the aqueous extract from leaves of Ageratum conyzoides showed a significant reduction of blood glucose level of 9.5% after 1hour and 21.3% after 4 hour.